Atypical presentation of Lyme neuroborreliosis related meningitis and radiculitis - Iman Dabiri; Nicholas Calvo; Feryal Nauman; Mahsa Pahlavanzadeh; Ahmet Z. Burakgazi (MDPI AG, 2019)
Lyme disease related central and peripheral nervous system manifestations can occur in isolation or together. Radiculitis or inflammation of the nerve root can be seen 3-5% of the time in acute neuroborreliosis affecting the PNS with a typical presentation and meningitis affecting the CNS is usually seen 1% of the time. The appropriate diagnosis and management of neuroborelliosis can be challenging and require meticulous medical approaches. Herein we present a unique case of Lyme disease with neurologic manifestations including both radiculitis and meningitis due to its atypical and challenging clinical presentation and management with updated literature review.